Hubungan Motivasi Belajar, Gaya Belajar dan Kesadaran Metakognitif dengan Hasil Belajar Biologi Siswa Kelas XI IPA SMA Negeri di Kabupaten Soppeng - Nia Hasniati; Mansyur Mansyur; Rachmawaty Rachmawaty (UNM Journal of Biological Education, 2017)
The research aimed (i) to describe learning motivation, learning style, metacognitive awareness and Biology learning results; (ii) to discover the relation between learning motivation and Biology learning results; (iii) to discover the relation between learning style and Biology learning results; (iv) to discover the relation between metacognitive awareness and Biology learning results; (v) to discover the relation of learning motivation, learning style, and metacognitive awareness simultaneously with Biology learning results of class XI IPA students at Public Senior High Schools in Soppeng District. The research is ex-post facto with the samples were 271 students. The results of the research revealed that (i) the students’ learning motivation is in fairly high category, (ii) the students’ learning style is dominated by kinesthetic learning type, (iii) the students’ metacognitive awareness is in well developed category, (iv) the students’ learning results are in high category, (v) there is relation between learning motivation and the Biology learning results with the score of correlation coefficient by 0.142, (vi) there is relation between learning style and the Biology learning results with the score of correlation coefficient by 0.331, (vii) there is relation between metacognitive awareness and the Biology learning results with the score of correlation coefficient by 0.358, and (viii) there is relation between learning motivation, learning style, and metacongitive awareness simultaneously with Biology learning results with the score of correlation coefficient by 0.398.